FREQUENCY OF VITAMIN D DEFICIENCY IN PATIENTS PRESENTING WITH FIBROMYALGIA: Vitamin D Deficiency in Fibromyalgia - Rashid, Samina; Nawaz, Khuram Haq; Fakhr, Amer; Ather, Hammad; Hakeem, Farzana; Yousaf, Rizwan (Pakistan Armed Forces Medical Journal, 2021)
Objective: To determine frequency of vitamin D deficiency in patients presenting with fibromyalgia and its association with various factors.Study Design: Cross sectional study.Place and Duration of Study: Medicine department, Pak Emirates Military Hospital Rawalpindi, from Sep 2018 to Feb 2019.Methodology: Ninety patients of fibromyalgia were included in the study. Diagnosis of fibromyalgia was made by the consultant rheumatologist on the basis of American College of Rheumatology Criteria needed for fibromyalgia diagnosis and classification. Vitamin D levels